Review of the book “Historical Journey to Brazil” (Geografares, 2026)
Review of the book “Historical Journey to Brazil”, by the French painter, artist and professor Jean-Baptiste Debret (1768–1848). Debret was part of the French Artistic Mission, led by Joaquim Lebreton and conceived during the reign of Dom João VI. He arrived in Brazil in 1816 and remained in the country until 1831. His works depict enslaved people, ethnographic themes, indigenous populations, clothing, urban landscapes, monarchs, utensils, religious ceremonies, natural areas, political events, fauna and flora, among other aspects of Brazilian daily life. His production constitutes a contemporary look at an ancestral Brazil, allowing the visualization of the past and reflection on the historical formation and current society.